Linear and curvature internal heterogeneous boundaries influences on mixed mode crack propagation using level set method - Abdolghafour Khademalrasoul (Iranian Society of Structrual Engineering (ISSE), 2017)
Interactive crack-internal heterogeneous boundaries have been of a great concern to researchers and engineers. Extended finite element method (X-FEM) has recently emerged as an approach to implicitly create a discontinuity based on discontinuous partition of unity enrichment (PUM) of the standard finite element approximation spaces. The extended finite element method (X-FEM) in the combination with level set method (LSM) has been utilized. In this contribution, predefined cracks and internal boundaries are created without meshing the internal boundaries. Soft/hard circular inclusions (interfaces), voids and linear interfaces are considered as internal discontinuities. In addition, the stress intensity factors for mixed mode crack problems are numerically calculated by using interaction integral approach. The interaction integral method is based on the path independent J-integral. The 4-noded rectangular element is considered to discretize the assumed plates. The effects of shape, size and schemes of internal boundary distributions are numerically simulated. The results are shown that the crack paths are attracted to soft internal boundaries and move away from the hard internal boundaries. Also, the influences of internal voids are much more than inclusions. In addition, the linear internal interface has affected the crack growth paths entirely and is created a complicate crack path. All numerical examples are demonstrated the flexibility and capabilities of X-FEM in the applied fracture mechanics